Imaging of patients with multiple myeloma and associated plasma cell disorders: consensus practice statement by the Medical Scientific Advisory Group to Myeloma Australia. Issue 10 (18th October 2021) - Creeper, Katherine; Augustson, Bradley; Kusel, Kieran; Fulham, Michael J.; Ho, Joy; Quach, Hang; Mollee, Peter; Weber, Nicholas; Talaulikar, Dipti; Johnston, Anna; Murphy, Nick; Joshua, Douglas; et al.
Abstract: Imaging modalities for multiple myeloma (MM) have evolved to enable earlier detection of disease. Furthermore, the diagnosis of MM requiring therapy has recently changed to include disease prior to bone destruction, specifically the detection of focal bone lesions. Focal lesions are early, abnormal areas in the bone marrow, which may signal the development of subsequent lytic lesions that typically occur within the next 18–24 months. Cross‐sectional imaging modalities are more sensitive for the detection and monitoring of bone and bone marrow disease and are now included in the International Myeloma Working Group current consensus criteria for initial diagnosis and treatment response assessment. The aim of this consensus practice statement is to review the evidence supporting these modalities. A more detailed Position Statement can be found on the Myeloma Australia website.